Eksplorasi Wawasan Pedagogis KH. Abdul Wahid Hasyim: Tinjauan Sistematis Terhadap Literatur Pendidikan - Firdaus, Aisyah; Hanum O. K., Azizah; Usiono , Usiono (Green Publisher Indonesia, 2024)
KH Abdul Wahid Hasyim is a prominent figure in Islamic education in Indonesia. This research explores his views on education, teaching methods, and their application in modern contexts. The aim is to understand his contributions deeply, evaluate the relevance of his concepts in current educational practices, and provide a foundation for innovation in progressive education systems. The research employs the Systematic Literature Review method to systematically explore Hasyim's pedagogical insights. Researchers gather, evaluate, and synthesize information from journals published between 2019-2024. Hasyim's educational perspective reflects the belief that education plays a strategic role in guiding individuals towards maturity, enhancing human dignity, and improving social conditions. The goal is to create individuals who are religious, knowledgeable, and intellectually sound, relevant in the modern educational context by integrating religious values with contemporary needs. Teaching methods like Wetonan, Sorongan, Hafalan, and Tutorial illustrate an adaptation between tradition and modernity, creating a holistic educational environment. According to Hasyim, teachers are agents of change, and students are active, creative, and independent learners. Hasyim's contributions in advocating inclusivity, liberalizing thought, reforming curricula, and establishing the Islamic University of Indonesia reflect his efforts to transform Islamic education to be more inclusive, progressive, and relevant to the times. Future research will focus on implementing Hasyim's teaching methods in modern education, evaluating the roles of teachers and students, and assessing his contributions to contemporary education, while promoting discussion forums to share thoughts on the implications of Hasyim's educational views in current educational practices.